2014
DOI: 10.1186/1746-1596-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Case report: intraductal tubulopapillary neoplasm of the pancreas with unique clear cell phenotype

Abstract: Intraductal tubulopapillary neoplasms of the pancreas are very rare tumors characterized by intraductal tubulopapillary growth, ductal differentiation, scant intracellular mucin production and cellular dysplasia. Here, we report the first case of an intraductal tubulopapillary neoplasm of the pancreas with clear cell morphology. The tumor was detected during the diagnostic work-up of acute pancreatitis in a 43- year old female. Histological examination revealed a tumor with the typical architecture of an intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Marked cytologic atypia was reported by most authors, with the exception of Zhao et al [8] who reported bland cells without significant atypia which were attributed to sampling issue. Cells with clear cell features were reported by Ahls et al [10]. Our case was similar to most of the published reports.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Marked cytologic atypia was reported by most authors, with the exception of Zhao et al [8] who reported bland cells without significant atypia which were attributed to sampling issue. Cells with clear cell features were reported by Ahls et al [10]. Our case was similar to most of the published reports.…”
Section: Discussionsupporting
confidence: 82%
“…In the data published (table 1), ITPN showed no sex prediliction, occurred in an age range of 35-80 years and was frequently located in the head and body of the pancreas [1,3,4,5,6,7,8,9,10,11,15]. On imaging studies, it presented as positron emission tomography (PET)-avid, as a cystic mass on computed tomography and as a hypoechoic mass on EUS.…”
Section: Discussionmentioning
confidence: 99%
“…Expressions of HMB-45 and smooth muscle actin support a diagnosis of PEComa, 16 whereas expressions of cytokeratin, CD10, and PAX8 favor a diagnosis of CCRCC. 10 Recently, a clear cell type of intraductal tubulopapillary neoplasm 18 has been described where the tumor closely resembles a metastatic CCRCC to the pancreas and exhibits a proliferation of clear cells within the pancreatic duct. The mimicry is further heightened by the neoplasm's ability to react positively to antibodies against carbonic anhydrase IX and CD10 on immunohistochemistry.…”
Section: Pathologic Differential Diagnosesmentioning
confidence: 99%
“…[3][4][5][6][7] Cases with atypical histological findings have also been reported. 4,[8][9][10][11] Here we describe the first case of ITPN with duodenal invasion and extensive calcification with foamy macrophage aggregation.…”
mentioning
confidence: 93%